PENGELOLAAN BARANG INVENTARIS PEMERINTAH DAERAH DI SEKRETARIAT DAERAH KABUPATEN POSO - Fahmi, Fahmi (Katalogis, 2017)
This study aims to identify and analyze the management of inventory Blood Governments in Poso regency Regional Secretariat, referring to the opinion of Peter and Yenny (2001: 21) that, management is a process that includes planning, regulation and control as well as maintenance. This research is descriptive qualitative, based on data collected through interviews and observation and documentation, it was concluded that, management of inventory in Poso regency Regional Secretariat, has not met the aspects of planning, regulation and control and good maintenance. The tendency of every unit within the Secretariat Poso regency, in planning for the needs of inventory items adapted to the available budget, and not because of an urgent need. There are no regulations on management of inventory in the form of technical guidelines stipulated by local laws or regulations Regent. Dalamrangka control inventory management has not been effective even when applied to the way any room units make room inventory cardÂ attached to a particular place which is easily seen. Maintenance of inventory items belonging to the region is still based on Regulation of the Minister of Home Affairs No. 17 of 2007, due to the lack of regulation of Regent and Regent Decision on guidelines for the technical management of inventory belonging to the area. Still there are some forces in the work unit environment of the Regional Secretariat who do not know their obligation to report property maintenance area.